1998
DOI: 10.1016/s0009-9236(98)90044-3
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin kinetics and dynamics during oral and rectal treatment of uncomplicated malaria*

Abstract: The similarity in parasite clearance times despite lower drug levels during rectal treatment suggests that initial oral doses may be unnecessarily high. The singular time dependency of artemisinin pharmacokinetics, attributed to autoinduction of drug elimination, has possible implications for combination chemotherapy. Decreasing artemisinin concentrations during treatment may partly explain recrudescences and increase the risk for resistance development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 22 publications
(3 reference statements)
7
71
2
Order By: Relevance
“…This may partly be explained by induction of enzymatic transformation of artemisinin and the consequent decline of blood concentrations after repeated doses. 3,4 This could be confirmed by studying whether introducing drugfree intervals could overcome the problem of enzyme induction. There are a number of unanswered questions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may partly be explained by induction of enzymatic transformation of artemisinin and the consequent decline of blood concentrations after repeated doses. 3,4 This could be confirmed by studying whether introducing drugfree intervals could overcome the problem of enzyme induction. There are a number of unanswered questions.…”
Section: Discussionmentioning
confidence: 91%
“…This phenomenon has been observed in patients treated with artemisinin, artemether (with a concomitant increase of the plasma concentrations of its metabolite dihydroartemisinin), and dihydroartemisinin after intake of artesunate. [3][4][5][6] In comparison with primarily single-dose studies in healthy humans, the results indicate that the decline of plasma concentrations is drug related. In the case of dihydroartemisinin taken orally, data suggest that the decline of plasma concentrations down to values observed in healthy subjects is a disease-related effect (Le NH and others, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin has a short elimination half-life, a rapid onset of action, no major side effects, and markedly induces of its own metabolic elimination, resulting in five-to sevenfold decreases in its concentrations over 5 to 7 days of administration in both malaria patients and healthy subjects (1,(3)(4)(5). A major drawback with artemisinin and its derivatives is the high recrudescence rates within 2 to 3 weeks after monotherapy (14,17).…”
mentioning
confidence: 99%
“…There is also evidence of true recrudescence, as determined by a PCR technique with patients treated with a combination of artemether and benflumetol (10) as well as artesunate alone (18). It has been suggested that the occurrence of recrudescence may partly be due to the decreasing artemisinin concentrations toward the end of treatment (4). Thus, the time-dependent kinetics of the drug can be of importance in dosing suggestions.…”
mentioning
confidence: 99%
See 1 more Smart Citation